Prepare Your Property for Hurricane Season - Chris Demers; Michael Andreu (EDIS)
Hurricane season is June 1 through November 30. Powerful storms that venture inland can damage forest and agricultural land and enterprises. There is no way to fully prepare for major devastation in advance, but this publication provides some strategies and steps you can take to get yourself and your land ready so that you can recover as quickly and smoothly as possible after a major storm.